Cross-border Banking and the Circumvention of Macroprudential and Capital Control Measures - Cerutti, Eugenio; Zhou, Haonan (Washington, D.C. : International Monetary Fund, 2018)
We analyze the joint impact of macroprudential and capital control measures on cross-border banking flows, while controlling for multidimensional aspects in lender-and-borrower-relationships (e.g., distance, cultural proximity, microprudential regulations). We uncover interesting spillover effects from both types of measures when applied either by lender or borrowing countries, with many of them most likely associated with circumvention or arbitrage incentives. While lender countries' macroprudential policies reduce direct cross-border banking outflows, they are associated with larger outflows through local affiliates. Direct cross-border inflows are higher in borrower countries with more usage of macroprudential policies, and are linked to circumvention motives. In the case of capital controls, most spillovers seem to be present through local affiliates. We do not find evidence to support the idea that additional capital inflow controls could interact with macro-prudential policies to mitigate cross-border spillovers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet